VERBAL COMMUNICATION IN BAHASA INDONESIA: A CASE STUDY ON ABAY (A FIVE-YEAR-OLD CHILD) - Maulidiyah, Lukluatul; Fahriany, Fahriany; Deni, Rahma (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2020)
ABSTRACT. Verbal communication is one of the ways for people to communicate each other. Components of verbal communication are sounds, words, language, and speech. Thus, In having a good verbal communication, people should master a target language. Moreover, there are two processes to comprehend and master a language which are acquiring and learning process.Hence, this study is aimed to observe how a-five-year old child acquire their verbal communiation in Bahasa Indonesia which become his second language. The participant of this study is a-five-year old child named Abay who has Madura language as his first language.The research uses qualitative data descriptively. A case study in this research was to provide a deeper understanding regarding the process of Abay’ verbal communication used in Bahasa Indonesia as the second language that he got from his environment. The data of this study are gathered through depth-interview and observation. Furthermore, the result of this study reveald that Abay could produce and acquire one of verbal communication form in Bahasa Indonesia which is interpersonal communication.